THE STYLE OF DIALOGUE IN THE STORY OF PROPHET SOLOMON AS IN SURAT AL-NAML (A STUDY OF ARABIC STYLISTICS IN THE QUR'AN) - Shofiyah, Naurotus; Taufiq, Mirwan Akhmad; Romdlon, Atiq Mohammad (An-Nas, 2025)
“This study aims to reveal and explain the stylistic features of the dialogue between Prophet Solomon, the Hoopoe bird, and Queen Bilqis in Surah Al-Naml, verses 20 to 44, to explore the beauty of the Qur'an from both its linguistic and semantic aspects. This research is a qualitative descriptive study. The primary source for this study is Surah Al-Naml, verses 20 to 44, while secondary sources include all relevant literature related to this research. Data collection was carried out using the method of intralinguistic equivalence, complemented by note-taking techniques. This study's findings reveal two sentence patterns in the dialogue between Prophet Solomon and the Hoopoe bird as well as Queen Bilqis: declarative sentences (kalam khabar) and imperative sentences (kalam insya'). The declarative expressions serve the purpose of conveying information and its inherent benefit. The study also identifies sentences that convey the meanings of contrast request and prayer, functioning as expressions of regret. On the other hand, imperative expressions reflect command, inquiry, and exclamation meanings. Additionally, sentences indicating astonishment or surprise were found.”